PENGARUH KOMPETENSI, DAN INDEPENDENSI TERHADAP KUALITAS AUDIT DENGAN MOTIVASI SEBAGAI VARIABEL PEMODERASI - Pairingan, Agustina; Allo Layuk, Paulus Kombo; Pangayow, Bill J.C (Fakultas Ekonomi, Universitas Cenderawasih, 2018)
Audit quality is concerning auditors’ ability in examining and reporting misconduct in accounting system that could affect the interest parties, therefore quality of audit is significantly related to the competence, independence and motivation of auditors in conducting an audit procedures. The objective of this paper is to determine the effect of competence and independence on audit quality with motivation as a moderating variabel. In this research, employees of inspectorate office at Papua Province and the employees of Financial and Development Supervisory Agency of Papua Province are involved as a population and 40 people are assembled as the respondents who have been participated in the research construction. While, sampling method that is used for selecting the sampel is the census method, which is by distributing 40 questionnaires for all the populations. The results in this study show that compentence has a significant impact on the audit quality. However, the independence variable has not significant effect on the audit quality. In addition, competence and independence simultaneously have not significant effects on the audit quality when they have been moderated by motivational variables.